From Risk Perception to the Use of Technical Restrictions of SVoD Services in Mexico, the Mediating Role of Parent Involvement and Knowledge - Sada Garibay, Cecilia; Lapierre, Matthew A. (Taylor and Francis Group, 2023)
Using parental mediation and protection motivation theory, a serial moderated mediation model was developed to study what drives parents to employ technical restriction tools offered by Subscription Video on Demand (SVoD) services. Based on a survey of 1,022 parents of elementary school children (generally between the ages of 5–12) in Mexico, it was found that for Netflix and Amazon Prime Video, the use of technical restrictions appears to be triggered by parents’ perception of risk and that parental involvement in children’s media use and perceived knowledge of the available technical restrictions mediates the usage of the parental control tools. ©The authors ©Taylor and Francis Group.